Modeling of image processing algorithms for hardware-software co-simulation - Isa, Ibrahim (2015)
Implementation and verification of algorithms such as image processing algorithms via deploying into field programmable gate arrays can be time consuming and involves a lot of technical complexities. Modern digital systems are expanding in terms of size and design complexity which becomes even more complicated due to task division between hardware and software as well as design and verification teams. Therefore this project proposes to model image processing algorithm such as human skin detection algorithm for hardware-software co-simulation. The skin detection algorithm was first designed as pure software followed by software profiling process to identify the compute-intensive modules. This was followed by the design of hardware accelerators for the compute-intensive modules and hardware-software co-simulation of the whole system.The hardware which is designed using SystemVerilog and the software which is in c programming language communicate through direct programming interface(DPI-C). MATLAB is used as the golden reference model to verify the hardware-software co-simulation. The co-simulation and verification process is automated with the aid of the MATLAB engine. When the hardwares-oftware co-simulation was implemented a speed improvement of up to 2.5 times was obtained as compared to pure software implementation.